First records of Thyone inermis and Labidoplax buskii (Echinodermata: Holothuroidea) in Canadian waters. (18th November 2014) - Massin, Claude; Robar-Matheson, Ashley; Hamel, Jean-François; Mercier, Annie
Abstract : This work presents records of two endobenthic species of sea cucumber (Holothuroidea: Echinodermata) not previously reported in Canadian waters. Thyone inermis (Dendrochirotida) and Labidoplax buskii (Apodida) were collected south-west of Nova Scotia (eastern Canada) in 2009 in Georges and Crowell Basins in the upper 2 cm of muddy seafloor at upper bathyal depths (240–370 m). Both species are of small size, 3.7–8 mm and 5–8 mm long, respectively.